Analisis Ratifikasi Persetujuan Kemitraan Ekonomi Komprehensif antara Indonesia dan EFTA - Ahmad Wildan Ali Fikri (Terang : Jurnal Kajian Ilmu Sosial, Politik dan Hukum, 2025)
Ratification is the formal process by which a country approves and legally ratifies an international agreement. Ratification was first introduced at the Vienna convention. The ratification of IE-CEPA was realized by the ratification of Law Number 1 of 2021 in accordance with the contents of Article 11 of the 1945 Constitution for the sake of the welfare of society. This research aims to determine the content of IE-CEPA and its impacts on Indonesia. This research uses normative research methods and is presented descriptively analytically. The results of the research conclude that this ratification has fulfilled the standards of international agreements and also the contents of the 1945 Constitution. Apart from that, this ratification has an impact on law, namely the obligation to harmonize national law and the economic impact which is marked by an increase in the trade graph of both parties.